The Effect of Visual Reasoning on Arithmetic Word Problem Solving - Ana-Maria Purcar; Mușata Bocoș; Alexandra-Lucia Pop; Alina Roman; Dana Rad; Daniel Mara; Claudia Crișan; Ramona Răduț-Taciu; Elena-Lucia Mara; Ioana Todor; Letiția Muntean-Trif; Mihaela-Gabriela Neacșu; et al. (MDPI AG, 2024)
First-grade students often encounter challenges in understanding and solving arithmetic word problems due to their limited reading comprehension abilities. Despite these difficulties, students may employ arbitrary strategies, such as combining numbers based on specific keywords, even if they lack a full understanding of the problems. Research suggests that effective mathematical reasoning involves the use of visual mental representations during the problem-solving process. To address this, some studies have explored methods to enhance students' comprehension of word problems. Building on this, the current study explores the impact of first-grade pupils creating visual representations of problem situations on their comprehension and the number of correct solutions. In a typical math class, 45 first graders received a paper-and-pencil task, and, in a visual context, they solved similar problems after reading and illustrating the situation. The findings reveal that while most participants correctly represented the problem situations through drawing, about half struggled to determine the numeric solutions. Nevertheless, the visual context led to an increase in the number of correct problem solutions compared to the normal context, suggesting the potential benefits of incorporating visual representations in enhancing comprehension and problem-solving skills.